Selection indicators of sustainability in the Atlantic Forest fragments in basin hydrographic River Poxim through the geoprocessing - Costa, Cristiano Cunha; Gomes, Laura Jane; Almeida, Antônio Pacheco de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The Brazilian Atlantic forest degradation resulted in a mosaic of forest fragments, compromising natural resources. The maintenance of forest cover allows maintaining the level of water in rivers and biodiversity. This paper aims at the selection of sustainability indicators in forest fragments of Atlantic Forest in the river basin Poxim through geoprocessing, aiming to support recovery strategies and conservation of these fragments. We used to aerofotografias corresponding to the year 2004 and projection UTM, Zone 24 South Datum and DSS-69. The selection of sustainability indicators is related to the use and occupation vectorized through tools of Geographic Information System (GIS), in this case the program ARCGIS 9.2, allowing to identify and quantify environmental sustainability indicators in the river basin Poxim. In the basin there are only 01 reserve with 198.84 hectares, demonstrating the failure of the Brazilian Forest Code (1965). Of the total existing riparian forest, less than half (46.22%) is in accordance with the Brazilian Forest Code. The forest fragments suffer serious impacts on agriculture of sugar cane and pasture. With the selection of indicators, it is possible to monitor and evaluate the behavior of these indicators, we can state that the agroecosystem is sustainable over time.